Pengaruh Modifikasi Ground Plane Pada Antena Mikrostrip dengan Teknik Meader Line - Catra Indra Cahyadi; Mutiara Widasari Sitopu; I Gusti Agung Ayu Mas Oka (Website, 2021)
Microstrip antennas generally have deficiency with small bandwidth, so that their utilization is very minimal and rarely used for antenna user applications on electronic devices. To increase antenna performance parameters bandwidth, voltage standing wave ratio, and return loss, need modification of antenna. This research was carried out by modifying of microstrip antenna with the meader line technique by ground plane wich is useful for increasing performance of microstrip antenna parameters. The ground plane on antenna was modified by adding a copper wire to the antenna. With modifications to ground plane antenna, the antenna performance parameters bandwidth, voltage standing wave ratio and return loss have decreased significantly. Antenna bandwidth has 124 MHz before modification, but has increased upto 214 MHz after modification ground plane, voltage standing wave raio has decreased from 1.835 to 1.12 after modifications ground plane antenna, and return loss of antenna before modification has -10.112 dB, after modification it decreased significanty upto -24.69 dB.